Improved multivariate statistical process control for chemical process fault detection and diagnosis - 324410 Lam, Hon Loong (Skudai : Universiti Teknologi Malaysia, 2004)
Thesis (Master of Engineering (Chemical)) - Universiti Teknologi Malaysia, 2004